The role of detoxifying enzymes in field-evolved resistance to nitenpyram in the brown planthopper Nilaparvata lugens in China. (April 2017) - Zhang, Xiaolei; Liao, Xun; Mao, Kaikai; Yang, Peng; Li, Dongyang; Alia, Ehsan; Wan, Hu; Li, Jianhong
Abstract: The brown planthopper, Nilaparvata lugens, is one of the most economically important rice crop pests in Asia, and has developed resistance to various insecticides from most chemical groups including neonicotinoid insecticides. At present, nitenpyram is the primary insecticide for N. lugens control in paddy fields. Thus, the susceptibility of N. lugens field populations to nitenpyram is of concern because of its extensive application. In the present study, the LC50 values and the activities of the detoxifying enzymes of fifty-eight representative field populations of N. lugens were determined. The results showed that LC50 values of field populations of N. lugens varied from 0.45 to 6.44 mg a. i./L, revealing that N. lugens has developed a moderate level of resistance (resistance ratio, RR = 2.4–33.9-fold) to nitenpyram. The activities of the detoxification enzymes including cytochrome P450 monooxygenase (r = 0.394, P = 0.002) and esterase (r = 0.274, P = 0.037), showed significant correlations with the log LC50 values for the field populations of N. lugens . Moreover, piperonyl butoxide (PBO) showed obvious synergism (synergism ratio, SR = 1.6–2.1-fold) in the collected field populations. Obvious regional variation in nitenpyram susceptibility was detected among the field populations of N. lugens, suggesting that nitenpyram resistance has occurred in field populations of N. lugens in China, and the detoxification enzyme cytochrome P450 monooxygenase is more likely to a contributing factor to nitenpyram resistance. Highlights: Obvious regional variation in nitenpyram susceptibility was found among the field populations of N. lugens in China. Nitenpyram resistance has occurred in field populations of N. lugens in China. Cytochrome P450 monooxygenase is likely a contributing factor to nitenpyram resistance in field populations of N. lugens .